VOICES OF WORKING WOMEN IN ANITA NAIR’S LADIES COUPÉ - C. Nesavathy; George, Selva Mary Gokila S; Darshana, S. Fransta; Dani, A. Anishya; Mahisha, A. Annie Divya (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Liberation in economy is a sweet candy factor in a woman’s life. It is a common belief that unmarried employed women lead a happy, independent life. This claim is queried in Anita Nair’s Ladies Coupé. The paper discusses the crises faced by a woman who is forced to be the bread winner of her family. It exposes her lack of individual space, rights and freedom. Financial exploitation becomes an inevitable feature in the lives of these women. The paper urges the need for a comfortable family atmosphere which is supportive and comprehending to make an employed woman liberated.